Economic Hardship and Academic Pursuit: A Study of Students in Higher Education - Arafat, Md. Yeasir; Md. Mahbubul Alam; Namisa Tabassum; Fahmida; Ismit Jarin Riche; Subradeb Chakma (International Journal of Educational Sciences and Development, 2025)
Purpose Economic hardship remains a major barrier for students in higher education, affecting their learning experiences and academic outcomes. This study examines how financial difficulties influence students’ access to essential resources, academic performance, mental health, and overall progress. It also aims to highlight the strategies students use to cope with these challenges and the role of institutional support programs in helping them succeed. This research relies on secondary data collected from previous studies, reports, and institutional statistics. Through careful review and analysis of these sources, the study identifies key patterns and trends showing how financial constraints shape students’ academic experiences and opportunities. Findings The analysis reveals that students from low-income backgrounds often face difficulties accessing learning materials, technology, and campus activities, which can slow their academic progress and increase the risk of dropping out. At the same time, many students demonstrate resilience, self-motivation, and the ability to overcome challenges, especially when supported by targeted institutional programs. The findings underscore the importance of policy interventions and university-led support initiatives to ensure more equitable opportunities in higher education for financially disadvantaged students.